CIDA's policy for environment sustainability (CIDA HullCA, 1992)
Provides guidance to CIDA managers and staff on objectives for programming which support environmental sustainability. Informs CIDA's partners in Canada and developing countries of its objectives and encourages them to work together with CIDA in efforts to implement comprehensive and forward-looking programmes which promote environmental sustainable.
DC